2017
DOI: 10.1007/s00404-017-4587-2
|View full text |Cite
|
Sign up to set email alerts
|

Candidate biomarkers in the cervical vaginal fluid for the (self-)diagnosis of cervical precancer

Abstract: PurposeDespite improvement in vaccines against human papilloma virus (HPV), the causative agent of cervical cancer, screening women for cervical precancer will remain indispensable in the coming 30–40 years. A simple test that could be performed at home or at a doctor’s practice and that informs the woman whether she is at risk would significantly help make a broader group of patients who aware that they need medical treatment. Cervical vaginal fluid (CVF) is a body fluid that is very well suited for such a te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 150 publications
1
30
0
Order By: Relevance
“…Proteomic studies have been performed on cervicovaginal fluid to analyze and understand the role of the microbiota on the cervical region metabolism [87][88][89]. A study using proteomic data showed that dysbiosis causes cervicovaginal inflammation and detrimental changes within the mucosal barrier [90].…”
Section: Cervicovaginal Microbiota and Relationship To Viral Infectionmentioning
confidence: 99%
“…Proteomic studies have been performed on cervicovaginal fluid to analyze and understand the role of the microbiota on the cervical region metabolism [87][88][89]. A study using proteomic data showed that dysbiosis causes cervicovaginal inflammation and detrimental changes within the mucosal barrier [90].…”
Section: Cervicovaginal Microbiota and Relationship To Viral Infectionmentioning
confidence: 99%
“…α-actinin-4 might play a significant role in the detection of cervical cancer from cervical vaginal fluid. Although this method requires significant improvement, it provides an exciting prospect for the early diagnosis of cervical cancer (Van Ostade et al, 2018). Snoek et al (2019a) have demonstrated that collecting urine is more convenient and comfortable for patients than cervical scrapes and is a promising alternative testing material to screen for cervical cancer.…”
Section: Diagnostic Dna Methylation Biomarkers For Hpv-positive and Nmentioning
confidence: 99%
“…Systems biology makes it possible to approach the task of searching for biomarkers of cervical neoplasia development more comprehensively. Postgenomic methods, including proteomics, are widely used for biomarker discovery in different biofluids: blood, cervicovaginal fluid (CVF), cerebrospinal fluid, peritoneal fluid, saline, urine, and etc . In oncology, protein/peptide panels were proposed for diagnosis of ovarian cancer, breast cancer, lung cancer, and etc.…”
Section: Introductionmentioning
confidence: 99%
“…CVF proteome was shown to change in different genital tract diseases (bacterial vaginosis, vaginitis, cervicitis, premature rupture of membranes, and neoplastic changes of cervix) . Alpha‐actinin‐4, pyruvate kinase M1/M2 isozyme, and S100A9 were proposed as promising markers of the cervix malignant process . Thus, CVF demonstrates a high potential for the search for biomarkers of the HPV‐associated cervical transformation, risk of disease progression, treatment monitoring, and new therapeutic targets .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation